Sexual health literacy among Slovenian secondary school students - Šporin, Marta (Obzornik zdravstvene nege, 2024)
Introduction: Sexuality education for adolescents is an important area of education. The aim of this study was to assess the knowledge of Slovenian upper secondary school students about sexuality, as well as their experiences, behaviours, and sources of information about sexuality. Methods: An invitation to complete an online questionnaire for first-year students was sent to all secondary schools in central Slovenia. The responses of 201 participants were included in the analysis. The average age of the respondents was 15.59 years; 57% of the participants were female and 67% attended general upper secondary school. The data were statistically analysed using chi-square, Mann-Whitney U, and t-test.Results: Respondents cited the internet (67.0%) and friends (60.4%) as the most common sources of information on sexuality. Most respondents expressed a preference for seeking information from healthcare professionals (61.2%) and least from teachers (26.5%). Sexual experiences involving vaginal penetration were found to be more frequent among students enrolled in vocational and technical education programmes than those attending general upper secondary education programmes (?2 = 7.863, p = 0.005). Knowledge about sexuality was found to differ by gender (U = 2257.500, p = 0.003) and type of secondary school (U = 1943.500, p = 0.001). Knowledge about sexuality was positively associated with the frequency of discussions about various sex-related topics, with the exception of petting. It was, however, not associated with sexual activity or the use of protection.Discussion and conclusion: More attention needs to be paid to the provision of sexuality education for secondary school students. School nurses can promote information sharing among peers, empower parents to engage in discussions on these topics with their adolescent children, and provide sexuality education in the school setting. Our study findings on the effectiveness of different forms and contents of sexuality education can serve as a basis for enhancing the existing preventive programmes.
Keywords: adolescents; contraception; kontracepcija; mladostniki; sex education; sexual health; sexually transmitted infections; spolna vzgoja; spolno prenosljive okužbe; spolno zdravje